2015
DOI: 10.2174/1573395511666150707181644
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuritis: A Model for the Immuno-pathogenesis of Central Nervous System Inflammatory Demyelinating Diseases

Abstract: Evidence for the tenuous regulation between the immune system and central nervous system (CNS) can be found with examples of interaction between these organ systems gone awry. Multiple sclerosis (MS) is the prototypical inflammatory disease of the CNS and is characterized by widely distributed inflammatory demyelinating plaques that can involve the brain, spinal cord and/or optic nerves. Optic neuritis (ON), inflammatory injury of the optic nerve that frequently occurs in patients with MS, has been the focus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Activated T cells mature and expand clonally before dividing into effector cells and migrating through the bloodstream to breach the blood–brain barrier (BBB). Endothelial cells in the CNS microvasculature contain adhesion molecules, which activated T cells can attach to and penetrate [ 3 , 18 ]. The release of cytokines and other proinflammatory mediators aggravates the inflammatory environment, attracting more immune cells to the CNS and eventually leading to demyelination [ 3 , 21 , 22 ].…”
Section: Pathophysiology Of Optic Neuritis a Projection Of Ms Pathome...mentioning
confidence: 99%
See 2 more Smart Citations
“…Activated T cells mature and expand clonally before dividing into effector cells and migrating through the bloodstream to breach the blood–brain barrier (BBB). Endothelial cells in the CNS microvasculature contain adhesion molecules, which activated T cells can attach to and penetrate [ 3 , 18 ]. The release of cytokines and other proinflammatory mediators aggravates the inflammatory environment, attracting more immune cells to the CNS and eventually leading to demyelination [ 3 , 21 , 22 ].…”
Section: Pathophysiology Of Optic Neuritis a Projection Of Ms Pathome...mentioning
confidence: 99%
“…Structural and functional abnormalities in the visual system are targeted in most patients with MS, typically at the earliest stages of the disease, defining a hallmark feature of MS, namely optic neuritis (ON). The evolution of the clinical picture of patients with MS is extremely variable and heterogeneous in terms of locations and extensions of brain and spinal cord lesions [ 3 ]. ON is an inflammatory injury of the optic nerve that leads to visual disability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1× AMP cells given by IV administration (N = 7), and 3× AMP cell treatments given by IP (N = 6) or IV (N = 9) injection all showed a significant (***p < 0.001) attenuation of EAE clinical scores as compared with vehicle-treated EAE mice, whereas 1× treatment with AMP cells by IP injection (N = 6) did not significantly reduce EAE scores. Data represent mean ± SEM and MS optic neuritis [34][35][36][37][38]. To evaluate inflammation in the optic nerve, control, EAE, and AMP cell-treated mice were sacrificed on day 42 p.i.…”
Section: Amp Cells Suppress Optic Nerve Inflammation and Demyelinationmentioning
confidence: 99%
“… 5 Immunized C57BL/6 mice develop a chronic disease in which motor disability onset is generally around 14 dpi and ON is often detected. 6 It has been reported that in the optic nerve, where the volume to surface ratio of myelin is quite low, MOG expression is increased compared to other proteins such as proteolipid protein (PLP), which is concentrated on the compact myelin. 7 Functional damage of the anterior visual system can be detected with Visual Evoked Potential (VEP) and Electroretinogram (ERG), while Optical Coherence Tomography (OCT) is used to evaluate structural retinal alterations.…”
Section: Introductionmentioning
confidence: 99%